2018
DOI: 10.29252/jhsme.5.4.22
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Professional Behavior among Dental Students: A Case Study on Shahid Sadoughi University of Medical Sciences in Yazd and Qom University of Medical Sciences in Qom, Iran

Abstract: Introductionrofessional behavior is defined as the ability of meeting the ethical expectations of patients. These expectations are based on patients' welfare, independence, and social justice. This type of behavior is determined by commitment to professional duties, adherence to ethical principles, and sensitivity toward patient community (1).One of the main duties of medical universities is to prepare students to comply with professional standards (2). Similar to any other profession, dentistry requires a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Also, there was no significant difference between male and female students regarding moral skills. This is consistent with Razeghi et al [15], Gorter and Eijkman [25], and Jafari Nadoushan et al [16].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Also, there was no significant difference between male and female students regarding moral skills. This is consistent with Razeghi et al [15], Gorter and Eijkman [25], and Jafari Nadoushan et al [16].…”
Section: Discussionsupporting
confidence: 92%
“…Single students had significantly higher moral sensitivity, which agrees with Razeghi et al [15], especially in the domain of moral courage. In contrast, Jafari Nadoushan et al [16] and Gorjidooz and Greenman [27] reported no significant relationship between behavioral skills and marital status.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation